Improved Stabilization for Continuous Dynamical Systems with Two Additive Time‐Varying Delays. Issue 6 (20th March 2015) - Xiong, Lianglin; Li, Yongkun; Zhou, Weihong
Abstract: This paper studies the problem of stabilization criteria for systems with two additive time‐varying delays. First, the delay‐dependent stability condition for the systems is established through computing the more general Lyapunov functional. The Lyapunov functional is constructed by making full use of the property and the information of the systems, and the condition has advantages over the existing ones in the skillful combination of the delay decomposition and the reciprocal convex approach. Second, considered to be more flexible for the controller design with the introduced positive scalar, a new controller method is presented. Finally, two examples are provided to demonstrate the advantage of the results in this paper.